Immune function of Zhenqi Fuzheng capsule on volleyball players after high intensity training - Wang, L.; Wang, H.; Tuo, W. (Revista Brasileira de Medicina do Esporte, 2021)
At present, many studies have proved that proper exercise can promote the immune function of human body to a certain extent, but athletes need a lot of high-intensity sports training, and their immune function declines instead of improving. In order to control the decline of immune function of athletes after high-intensity training, this study propose the Zhenqi Fuzheng capsule to achieve this goal. Through experimental comparison, the parameters such as white blood cell content, immunoglobulin number, T lymphocyte, human hemoglobin content and exercise exhaustion time were detected after high-intensity training. The results showed that compared with the control group taking Zhenqi Fuzheng, the weight of those who had taken qifuzhengs capsule did not change, and the content of white blood cells, immunoglobulin, hemoglobin content and exercise time increased to a certain extent. The results showed that Zhenqi Fuzheng could inhibit the decrease of body immune function after high-intensity exercise, then accelerate the recovery of human immune function. This study is expected to enhance the immunity of sports athletes, and reduce athletes` pain after high-intensity training.